2014
DOI: 10.1186/1471-2202-15-10
|View full text |Cite
|
Sign up to set email alerts
|

Differences in somatosensory processing due to dominant hemispheric motor impairment in cerebral palsy

Abstract: BackgroundAlthough cerebral palsy (CP) is usually defined as a group of permanent motor disorders due to non-progressive disturbances in the developing fetal or infant brain, recent research has shown that CP individuals are also characterized by altered somatosensory perception, increased pain and abnormal activation of cortical somatosensory areas. The present study was aimed to examine hemispheric differences on somatosensory brain processing in individuals with bilateral CP and lateralized motor impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
0
28
0
2
Order By: Relevance
“…The majority of abnormal cortical SEPs occurred in children with acquired dystonia, which is not surprising. Abnormal SEPs have been reported in children with ‘spastic’( Tomita et al, 2006 , Riquelme et al, 2014 ) and athetoid CP ( Tomita et al, 2006 ), but not specifically in dystonic CP or other forms of acquired dystonia. Indeed there is a paucity of published neurophysiological data in children with dystonia or dyskinetic cerebral palsy ( McClelland, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of abnormal cortical SEPs occurred in children with acquired dystonia, which is not surprising. Abnormal SEPs have been reported in children with ‘spastic’( Tomita et al, 2006 , Riquelme et al, 2014 ) and athetoid CP ( Tomita et al, 2006 ), but not specifically in dystonic CP or other forms of acquired dystonia. Indeed there is a paucity of published neurophysiological data in children with dystonia or dyskinetic cerebral palsy ( McClelland, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it is not possible to conclude from these data that the sensory abnormalities are causal, it is likely that disruption of sensory pathways contributes to the disordered motor control in these children. Several studies have demonstrated anomalous sensory processing in children with “spastic” CP ( Riquelme and Montoya, 2010 , Kurz et al, 2014 , Kurz et al, 2015a , Riquelme et al, 2014 ) and these abnormalities do appear to have functional importance ( Kurz et al, 2015b ). There is clear evidence that primary dystonia is a network disorder involving multiple brain regions, including the cerebellum and sensorimotor cortex ( Neychev et al, 2011 , Neumann et al, 2015 ) and is a disorder of sensorimotor integration ( Hallett, 1995 , Tinazzi et al, 2000 , Abbruzzese et al, 2001 , Frasson et al, 2001 , Abbruzzese and Berardelli, 2003 ; Tinazzi et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In hemiparetic CP, reduced and altered patterns of spontaneous movement may be due to abnormal sensory feedback, altered cortical reorganization of sensorimotor function and/or abnormal sensory-motor integration. These can all lead to asymmetric somatosensory processing deficits [ 58 ]. Several studies in healthy and stroke groups have discussed the lateralization of sensorimotor function in the hemispheres, where the left hemisphere is associated with visual feedback [ 52 ] and initial trajectory features (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown better outcomes in younger primates following unilateral lesions in the motor cortex [ 61 ]. Previous neuroimaging studies have reported significant alterations in white matter pathways connecting to the somatosensory cortex, suggesting that CP disrupts sensory and motor pathways [ 58 , 62 , 63 ]. One study of children with unilateral CP found that proprioception, pain and touch sensitivity did not differ between children with left versus right motor impairments, but lip and thumb stimulation in the left motor impaired group elicited smaller beta power and more symmetrical somatosensory evoked potential amplitude, suggesting different mechanisms of sensorimotor reorganization [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, the integrity of sensory information has been demonstrated to be necessary for satisfactory performance of precision grip tasks, [7][8][9] and up to 90% of children with USCP may have some degree of sensory impairment. 4 In addition to the deficits of tactile perception, children with CP also present an abnormal brain processing of somatosensory stimulation, 10 as well as an atypical response of the somatosensory cortices to external stimuli with a negative correlation found between the amount of errors in a motor task performance and the efficacy of the somatosensory cortices synchronization. 11 Considerable attention has been paid in the literature to improving upper-extremity motor abilities.…”
mentioning
confidence: 99%